2021
DOI: 10.1186/s12877-021-02618-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated primary care and social services for older adults with multimorbidity in England: a scoping review

Abstract: Background As the prevalence of older adults with multimorbidity increases, greater integration of services is necessary to manage the physical and psycho-social needs of this cohort. This study describes and summarises current evidence, clinical provision and progress towards integrated primary care and social services for older adults with multimorbidity in England. Methods A scoping review was conducted involving systematic searches of a range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…The data gathered by the review were iteratively synthesised descriptively, using counts to summarise article characteristics (that set out the number, type and quality of studies extracted); use of the data charting technique; and through interpretation of the findings by sifting and sorting material [ 25 ]. The main environmental determinants identified by the review were collated and presented below.…”
Section: Methodsmentioning
confidence: 99%
“…The data gathered by the review were iteratively synthesised descriptively, using counts to summarise article characteristics (that set out the number, type and quality of studies extracted); use of the data charting technique; and through interpretation of the findings by sifting and sorting material [ 25 ]. The main environmental determinants identified by the review were collated and presented below.…”
Section: Methodsmentioning
confidence: 99%
“…The data gathered by the review were iteratively synthesised descriptively, through the use of counts to summarise article characteristics (that set out the number, type, and quality of studies extracted and collated social care need variables identified), the data-charting technique, and interpretation of the findings by sifting and sorting material. 14 The main social care need variables identified were collated and are presented in Supplementary Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…The data gathered by the review were iteratively synthesised descriptively, using counts to summarise article characteristics (that set out the number, type, and quality of studies extracted), the data charting technique and interpretation of the findings by sifting and sorting material (19). The main environmental factors identified were collated and presented below.…”
Section: Summarising and Analysismentioning
confidence: 99%